2003
DOI: 10.1177/002204260303300310
|View full text |Cite
|
Sign up to set email alerts
|

Ascertaining the Need for a Supervised Injecting Facility (SIF): The Burden of Public Injecting in Montreal, Canada

Abstract: Empirical evidence suggests that a key prerequisite for a supervised injection facility (SIF) utilization is the existence of an “open drug scene,” where users publicly inject drugs. This study seeks to determine the extent and profile of public injecting among injecting drug users (IDUs) in Montreal, Canada, where pilot SIFs are under consideration. A cross-sectional study of IDUs who injected publicly at least once in the previous month was appended to an HIV-risk surveillance study among Montreal IDUs (Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 13 publications
5
24
0
10
Order By: Relevance
“…The prevalence of any recent public injecting in our sample (71.9%) was comparable to findings among people who inject drugs in Canada's largest cities, 3,5,6 and almost 1 in 2 participants (46.4%) reported that at least one-quarter of their recent injections took place in public or semipublic settings. Consistent with prior research, [1][2][3][4]6 regular public injecting was independently positively associated with homelessness or unstable housing and high-intensity injection of both opioids and crystal methamphetamine. Although neighbourhood of use was not independently associated with public injecting, crude prevalence was significantly higher among those who reported that they usu- …”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The prevalence of any recent public injecting in our sample (71.9%) was comparable to findings among people who inject drugs in Canada's largest cities, 3,5,6 and almost 1 in 2 participants (46.4%) reported that at least one-quarter of their recent injections took place in public or semipublic settings. Consistent with prior research, [1][2][3][4]6 regular public injecting was independently positively associated with homelessness or unstable housing and high-intensity injection of both opioids and crystal methamphetamine. Although neighbourhood of use was not independently associated with public injecting, crude prevalence was significantly higher among those who reported that they usu- …”
Section: Discussionsupporting
confidence: 74%
“…In the Canadian context, high levels of public injecting have been documented among people who inject drugs in Vancouver, [1][2][3] Ottawa, 4 Toronto 5 and Montréal, 6 where 54%-77% of people who inject drugs reported any recent public injecting, and 17%-23% reported injecting predominantly in public. Public injecting poses the risks of discovery by police, robbery and violence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Canada, injection drug use is reported among approximately 38% and 54% of street youth in Vancouver (Ochnio et al, 2001) and Montreal (Roy et al, 2002) respectively. Interestingly, there remains an absence of data on public injection drug use among street-involved youth, even though public injecting has been associated with extensive harms (e.g., HIV) among more experienced populations of homeless injectors both in our setting (Small et al, 2005) and others (Rhodes et al, 2006;Klein and Levy, 2003;Navarro and Leonard, 2004;Green et al, 2003). Further, given that homeless youth are a "hidden population" often not connected to any traditional health-related system (Feldman and Middleman, 2003;Martijn and Sharpe, 2006), little is known about rates of homelessness and the associated risks among street-involved youth.…”
Section: Introductionmentioning
confidence: 92%
“…A complete description of the development and validation of the evaluation tool can be found elsewhere [20]. Briefly, the 16 cases were selected from a pool of 60 unique experiences reported by IDUs as part of a study on public injecting [21]. Eleven medical experts in overdose recognition and treatment were asked to designate each case as either: (i) opioid overdose; (ii) non-opioid overdose; (iii) not an overdose; or (iv) not enough information/unsure, and whether naloxone was indicated.…”
Section: Evaluation Toolmentioning
confidence: 99%